What are the necessary conditions for muscle hypertrophy? - Mason, L. (1997)
In the text that follows, the anatomic structure and function of skeletal muscle will be briefly reviewed including information on: Structure of skeletal muscle - ultrastructure A review of muscle fibre types, characteristics and distribution in the human body The effects of training and adaptations to skeletal muscle